Development of a potentially probiotic food through fermentation of Andean tubers - Mosso, Ana Laura (2016)
With the aim to obtain a non-dairy solid probiotic product, three different Andean tubers -oca (Oxalis tuberosa), papalisa (Ullucus tuberosus) and potato (Solanum tuberosum spp andigena)- were assessed as fermentation substrates for the potentially probiotic L. brevis CJ25 strain. Fermented Churqueña potato puree, oregano and NaCl were used for the manufacture of a product called Potato Cheese due to its firm texture. This functional food contains a viable cell concentration of 8.0 log CFU/g and pH 5.1. Even after 28 days of storage at 4 °C, increases in cell counts were found and pH decreased 0.7 units, which improved food safety avoiding the growth of spoilage and pathogenic microorganisms. The in vitro tests indicated that L. brevis CJ25 exhibited high level of survival in simulated gastric juice (3 h, pH 2.5) when delivered in Potato Cheese, and also showed resistance to bile salt after 3 h of exposure. These results suggest that Potato Cheese is a promising novel functional food with high nutritional value, free of cholesterol and lactose and its development may have a favorable impact in Andean regional economies.